AN EDITORIAL ABOUT NEAR FUTURE IN ARCHITECTURE - Harsritanto, Bangun I. R. (MODUL, 2024)
On this Vol 24 no 2, MODUL has published 5 scientific articles. With compiling the information of all published articles, this editorial try to provide scientific information about “the near future” that might be paradoxal to each others